Vertical jump performance of professional male and female volleyball players: effects of playing position and competition level - Sattler, T.; Hadžic, V.; Derviševic, E.; Markovic, G. (The Journal of Strength and Conditioning Research, 2015)
Vertical jump (VJ) performance is an important element for successful volleyball practice. The aims of the study were (a) to explore the overall VJ performance of elite volleyball players of both sexes, (b) to explore the differences in VJ performance among different competition levels and different playing positions, and (c) to evaluate the sex-related differences in the role of the arm swing and 3-step approach with arm swing on the jump height. We assessed the VJ capacity in 253 volleyball players (113 males and 140 females) from Slovenian first and second Volleyball Division. The height of squat jump (SJ), countermovement jump, block jump, and attack jump was tested using an Optojump system. We observed significant differences (p = 0.05) in VJ height between different levels of play that were most pronounced in the SJ. Position-related differences in VJ performance were observed in male players between receivers and setters (p = 0.05), whereas in females, VJ performance across different playing positions seems equal. Finally, we found that male players significantly better use the arm swing during VJ than females (p = 0.05), whereas the use of eccentric part of the jump and approach before the spike to improve VJ performance seem to be equally mastered activity in both sexes. These results could assist coaches in the development of jumping performance in volleyball players. Furthermore, presented normative data for jump heights of elite male and female volleyball players could be useful in selection and profiling of young volleyball players.